2022
DOI: 10.3390/cancers14020452
|View full text |Cite
|
Sign up to set email alerts
|

Who’s Who? Discrimination of Human Breast Cancer Cell Lines by Raman and FTIR Microspectroscopy

Abstract: (1) Breast cancer is presently the leading cause of death in women worldwide. This study aims at identifying molecular biomarkers of cancer in human breast cancer cells, in order to differentiate highly aggressive triple-negative from non-triple-negative cancers, as well as distinct triple-negative subtypes, which is currently an unmet clinical need paramount for an improved patient care. (2) Raman and FTIR (Fourier transform infrared) microspectroscopy state-of-the-art techniques were applied, as highly sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
4
8
0
Order By: Relevance
“…As expected, the LA and LB samples have similar spectral profiles, suggesting similar constitution, as they have similar gene expression and biochemical constituents, with higher intensities in virtually all peaks compared to the normal tissue spectrum, but increased peaks of lipids, whereas the TN samples have higher intensities in peaks found approximately at 1100, 1300, and 1440 cm −1 , assigned to proteins (collagen). These results are consistent with the literature of Raman spectroscopy in evaluating molecular subtypes of breast cancer 38–44 . Bi et al 38 differentiated breast cancer cells HER2‐enriched and HER2 nonenriched, obtaining a sensitivity and specificity of 99%, respectively, and showed that HER2‐enriched cells had a higher lipid content due to exacerbated fatty acid and phospholipid synthesis.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…As expected, the LA and LB samples have similar spectral profiles, suggesting similar constitution, as they have similar gene expression and biochemical constituents, with higher intensities in virtually all peaks compared to the normal tissue spectrum, but increased peaks of lipids, whereas the TN samples have higher intensities in peaks found approximately at 1100, 1300, and 1440 cm −1 , assigned to proteins (collagen). These results are consistent with the literature of Raman spectroscopy in evaluating molecular subtypes of breast cancer 38–44 . Bi et al 38 differentiated breast cancer cells HER2‐enriched and HER2 nonenriched, obtaining a sensitivity and specificity of 99%, respectively, and showed that HER2‐enriched cells had a higher lipid content due to exacerbated fatty acid and phospholipid synthesis.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with the literature of Raman spectroscopy in evaluating molecular subtypes of breast cancer. [38][39][40][41][42][43][44] Bi et al 38 differentiated breast cancer cells HER2enriched and HER2 nonenriched, obtaining a sensitivity and specificity of 99%, respectively, and showed that HER2-enriched cells had a higher lipid content due to exacerbated fatty acid and phospholipid synthesis. Bendau et al 39 differentiated the collagen molecular characteristics between TN metastatic tumors and nonmetastatic tumors that are ER-positive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations